Yahoo奇摩 網頁搜尋

  1. nCr = n! / [(n-r)! * r!] 1. (n+3)! / (n+1)! = (n+3)(n+2)(n+1)! / (n+1)! = (n+3)(n+2) 2. nCn-1 * nCn = n! / [1! * (n-1)!] * n! / [0! * n!] = n * 1 = n 2014-03-12 13:21:19 補充: r 是 n-1,代入就是了。 nCn-1 = n! / {[n - (n-1)] * (n-1)!} = n! / (n-1)! = n 2014-03-12 15:04:23 補充: 多謝兩位老師幫手解釋...

    分類:科學及數學 > 數學 2014年03月17日

  2. My experience is to attack the leading term and the constant term. If there is no constant term, attack the term with lowest total degree. This may not be enough to help you. Will you be kind enough to list some example you know so that I can show you what did...

    分類:科學及數學 > 數學 2006年11月26日

  3. 18a2 +15b -50b2 -9a =2(3a)^2-2(5b)^2-9a+15b =2[(3a)^2-(5b)^2]-3(3a-5b) =2[(3a+5b)(3a-5b)]-3(3a-5b) =(3a-5b)[2(3a+5b)-3] =(3a-5b)(6a+10b-3)

    分類:科學及數學 > 數學 2008年01月14日

  4. ... k <= 6.977, there is no factor of 2^7 = 128 in the expression . Since 126 >= 5^k' gives k <= 3.005, there...

    分類:科學及數學 > 數學 2014年06月14日

  5. ab/c+d product= x sum= + 2009-12-03 03:25:13 補充: 多數都係divide by/into呢兩個文字都唔跟,唔知邊個大,不過常理應該係咁.

    分類:科學及數學 > 數學 2009年12月13日

  6. 我以為 8C9 會 define 為 0 較為妥當? 2014-03-12 14:28:49 補充: Yes, that is conventionally defined as 0. http://en.wikipedia.org/wiki/Combination 2014-03-12 16:48:26 補充: 太客氣啦~ nC0 = nCn = 1 是唯一方法 nC(n+1) = 0 = 0 個方法 = 沒有...

    分類:科學及數學 > 數學 2014年03月16日

  7. α + β = -5 and αβ = -1 (1) α2-αβ+β2 = (α + β)^2 - 3αβ = (-5)^2 - 3(-1) = 25+3 = 28 (2) (α-2β)(2α-β) = 2α^2 + 2β^2 - 5αβ = 2(α+β)^2 - 9αβ = 2(-5)^2 - 9(-1) = 50+9 = 59

    分類:科學及數學 > 數學 2007年11月13日

  8. ...: -8 = 1 - 9 = 1² - 3² (ii) Factorize the expression : m² - 2m - 8 = m² - 2m + 1² - 3² = m² - 2m(1...

    分類:科學及數學 > 數學 2020年07月31日

  9. 1)(a+b)^2-2(a+b) =(a+b)(a+b-2) 2)px+py-qx-qy =(x+y)(p-q) 3)3x+2y-12xz-8yz =(3x+2y)(1-4z) 4)xy-4y-5x+20 =y(x-4)-5(x-4) =(x-4)(y-5) 5)a^2-ab+ac-bc =(a-b)(a+c) 6)ab-a-pb+p =(a-p)(b-1) 7)(a+b)p-2a-2b =(a+b)(p-2) 8)p(a-b)-q(b-a) =(a-b)(p+q)

    分類:科學及數學 > 數學 2007年10月02日

  10. 1. (m-n)2 + n(n-m) =(m-n)2 - n(m-n) =(2-n)(m-n) 2. 4(a-b)3 – 12(b-a)2 =12(a-b) +24(a-b) =36(a-b) 3. -ab(rx-s) - ab2(s-rx)2 = -ab(rx-s) +4ab(rx-s) =3ab(rx-s) 2008-06-12 18:41:46 補充: 我無搞錯!投我一票!!!候選編號 001

    分類:科學及數學 > 數學 2008年06月15日